Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.12968/ijpn.2011.17.8.405
|View full text |Cite
|
Sign up to set email alerts
|

End of life in an Icelandic nursing home: an ethnographic study

Abstract: The findings suggest that RNs' professional knowledge can greatly contribute to the care of dying elderly residents in nursing homes. There seem to be many parallels between the condition and wellbeing of very frail nursing home residents and patients in specialized palliative care units for the elderly. Public awareness of palliative care of the elderly in Icelandic nursing homes should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…Nurses experienced that it was the nurse who was responsible for care planning and should have the competence to observe the patient’s condition and current needs, and it was the nurse whose task it was to facilitate multiprofessional cooperation. The element of care planning was only briefly mentioned in earlier studies (30), and care planning has not been defined to be an independent competence area (12,17). It is possible that care planning is considered to be a part of all care in general, and it has not been seen as a factor that has importance on its own.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses experienced that it was the nurse who was responsible for care planning and should have the competence to observe the patient’s condition and current needs, and it was the nurse whose task it was to facilitate multiprofessional cooperation. The element of care planning was only briefly mentioned in earlier studies (30), and care planning has not been defined to be an independent competence area (12,17). It is possible that care planning is considered to be a part of all care in general, and it has not been seen as a factor that has importance on its own.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses' competence to support the communication and continuity of care between the patient, their family and the physician is important (25,26). Within the organisation, nurses must have the competence to make sure that the care instructions are clear to all nurses, especially inexperienced ones (30). Nurses also need the ability to help patients and their families to participate in decision-making (23).…”
Section: Introductionmentioning
confidence: 99%
“…In a nursing home study based on participant observation data, it was found that care involving a palliative approach was the most important element of the care and that registered nurses had a key role in such care (Emilsdóttir & Gústafsdóttir, 2011). Another participant observation study focusing on older people’s end of life in nursing homes showed that nursing staff can influence the care relationship through how they behave in relation to the older person (Spichiger, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…By 2020, it is projected that half of all deaths in the United States will occur in NHs (Last Acts ). Therefore, in general, cognitively intact NH patients are in the last phase of life and might be in great need of palliative care (Emilsdóttir & Gústafsdóttir ), and the quality of that care will affect many individuals and their families worldwide.…”
Section: Introductionmentioning
confidence: 99%